TREATMENT OF PATIENTS WITH CHRONIC HEART FAILURE AND ANEMIA OR IRON DEFICIENCY - Вальчук, Дарья; Ханюков, Алексей; Песоцкая, Л.А.; Сапожниченко, Л.В.; Щукина, Е.С. (SWorldJournal, 2022)
Anemia and iron deficiency is widespread among patients with chronic heart failure (CHF) and is associated in such patients with reduced ability to exercise, a deterioration in the quality of life and a worse prognosis, regardless of the presence of anem